Migration Italy : the art of talking back in a destination culture - Parati, Graziella, 1960- (Toronto Italian studies, 2005)
In terms of migration, Italy is often thought of as a source country - a place from which people came rather than one to which people go. However, in the past few decades, Italy has become a destination for many people from poor or war-torn countries seeking a better life in a stable environment. Graziella Parati's Migration Italy examines immigration to Italy in the past twenty years and the cultural hybridization that has occurred as a result.